2015
DOI: 10.4187/respcare.03809
|View full text |Cite
|
Sign up to set email alerts
|

Bench Comparative Assessment of Mechanically Assisted Cough Devices

Abstract: BACKGROUND: Mechanically assisted cough devices are used in patients with impaired cough to avoid secretion accumulation. We compared 5 mechanically assisted cough devices by bench testing using a breathing simulator and assessed their user-friendliness. METHODS: We measured inspiratory and expiratory airway pressures and peak expiratory flow, the strongest indicator of cough efficacy. We performed 2 bench tests: 1) to ascertain the differences between preset and actual settings in 3 different machines of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…In the last years, mechanical assisted cough devices have been increasingly used in the acute setting; however, these devices aim to remove secretions from the large airways to the airway opening, through a sequential application of positive and negative (sub-atmospheric) pressure to the airway [37]. Differently, HFCWO aims to mobilize secretions from the smallest and deepest airways towards the upper and larger airways.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, mechanical assisted cough devices have been increasingly used in the acute setting; however, these devices aim to remove secretions from the large airways to the airway opening, through a sequential application of positive and negative (sub-atmospheric) pressure to the airway [37]. Differently, HFCWO aims to mobilize secretions from the smallest and deepest airways towards the upper and larger airways.…”
Section: Discussionmentioning
confidence: 99%
“…A bench study that compared 5 devices for their accuracy in delivering set pressures and set times to a lung model disclosed discrepancies in most MI-E models tested. 46 The investigators also found inconsistencies in the pressures delivered and their duration between different devices of the same model of in-exsufflator. Furthermore, the performance of each of the models was affected differently by alterations in lung mechanics and imposed leaks.…”
Section: Mechanical Insufflation-exsufflationmentioning
confidence: 99%
“…Thus, in the presence of air leaks, the set pressure is reached later, making the delay in the commencement of the oscillations greater. A recent study by Frigerio et al 28 found that the presence of air leaks can affect the performance of conventional MI-E. Another feature seen in the flow wave analysis and described previously 18 is that at the beginning of the pause after the end of exsufflation cycle, a drop in the flow wave occurs due to the elastic recoil of the lung.…”
Section: Discussionmentioning
confidence: 79%